Rancang Bangun Website Kasir Dan Manajemen Stok Untuk Distributor Utama Bumbu 47 Di Surabaya - Jocelyn Leora; Rinabi Tanamal (Universitas Multi Data Palembang, 2026)
The advancement of information technology has significantly impacted the food distribution industry. The main distributor of Bumbu 47 in Surabaya faces challenges in recording transactions and stock management, which are still done manually, leading to recording errors and low operational efficiency. This study develops a web-based application to automate these processes. The application is developed using the Waterfall method with Laravel, MySQL, as well as HTML, CSS, and JavaScript technologies. Testing results show that the system can automate transaction recording, update stock in real-time, and generate sales reports. The implementation of this application has had a positive impact on improving recording accuracy and operational efficiency for the distributor.